Menguji Peran Kapabilitas Inovasi sebagai Necessary atau Sufficient Condition dalam Menciptakan Keunggulan Bersaing UMKM: Pendekatan Fuzzy-Set Qualitative Comparative Analysis (fsQCA) - Muhammad Faiq; Tiara Iskandar (Ebisma (Economics, Business, Management, & Accounting Journal), 2026)
SME competitive advantage is influenced by multiple interacting conditions in shaping organizational outcomes. This study explores the roles of innovation capability, entrepreneurial competency, and business network in shaping competitive advantage using the fuzzy-set Qualitative Comparative Analysis (fsQCA) approach. Data were collected from SMEs in Jambi Province involving business owners or managers as respondents. The findings reveal that no single necessary condition determines competitive advantage. Innovation capability emerged as the dominant condition across all sufficient configurations, yet it did not operate independently without the support of entrepreneurial competency or business network. The analysis identified three sufficient configurations, namely the combination of innovation capability and entrepreneurial competency, the combination of innovation capability and business network, and the simultaneous combination of all three conditions. The configuration combining innovation capability, entrepreneurial competency, and business network demonstrated the strongest result in generating competitive advantage. The findings confirm that SME competitive advantage is shaped more by combinations of multiple conditions than by a single condition operating independently.